Differences of hip involvement in systemic and non-systemic juvenile idiopathic arthritis - L. S. Sorokina; I. S. Avrusin; R. K. Raupov; N. T. Garipova; M. M. Gharabaghtsyan; S. V. Khrypov; M. A. Kaneva; E. A. Isupova; E. V. Gaidar; I. A. Chikova; M. F. Dubko; V. V. Masalova; et al. (Научно-практическая ревматология)
Systemic corticosteroids are continued to be administered in juvenile idiopathic arthritis (JIA) patients, especially in systemic JIA (sJIA), despite the ability of biologic therapy. One of the complications of long-term CS treatment is delayed hip arthritis development with risk of secondary hip osteoarthritis formation and total hip arthroplasty (THA).We compared different types of hip joint lesions in JIA, especially, secondary hip osteoarthritis development and THA rates in systemic and non-systemic JIA, and evaluate systemic corticosteroids contribution to those complications.The study included 753 JIA patients. They were divided into 2 groups: patients with sJIA and non-systemic JIA (nsJIA). Clinical and demographic characteristics, CS treatment regimens were compared.Results. Hip arthritis was found equally often in both groups, but both secondary hip osteoarthritis (19% vs 5,3%) and THA (8.6% vs 1.6%) prevailed in the sJIA. Patients with sJIA had delayed hip involvement (57.9% vs 30.6%; p=0.019), earlier secondary hip osteoarthritis development (4.5 vs 5.1 years after the JIA onset) with younger age of secondary hip osteoarthritis achievement (13.7 vs 15.2 years; р=0.045), they also had higher inflammatory activity, greater systemic corticosteroids administration (94.8% vs 56.1%; р=0.0000001) and higher cumulative systemic corticosteroids dose (3085 mg vs 2000 mg; p=0,005). More than half patients (56.1%) with nsJIA had systemic corticosteroids treatment and impaired calcium-phosphorus metabolism.Conclusion. Systemic corticosteroid treatment and delayed hip involvement are independent predictors of secondary hip osteoarthritis in all JIA categories. Calcium and phosphate metabolism disturbances are additional predictor for secondary hip osteoarthritis in non-systemic JIA categories